2022
DOI: 10.1007/s00277-021-04732-4
|View full text |Cite
|
Sign up to set email alerts
|

Busulfan–fludarabine- or treosulfan–fludarabine-based myeloablative conditioning for children with thalassemia major

Abstract: Significant advances in supportive care for patients with transfusion-dependent thalassemia major (TDT) have improved patients' life expectancy. However, transfusion-associated iron overload remains a significant barrier to long-term survival with good quality of life. Today, allogeneic hematopoietic stem cell transplantation (HSCT) is the current curative standard of care. Alongside selection of the best available donor, an optimized conditioning regimen is crucial to maximize outcomes for patients with TDT u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
2
16
1
Order By: Relevance
“…Graft versus host disease was the major complication with grade II-IV acute and chronic incidence to range to about 24% and 13% respectively [186]. Similar results were obtained in other short and long term monitoring studies of HSCT TM patients [7,[182][183][184]187]. Overall, it appears that in general young and non-iron loaded patients with nonunderlying co-morbidities have the highest prospects of OS and TFS from the HSCT TM patients.…”
Section: Endocrine Glandssupporting
confidence: 78%
See 1 more Smart Citation
“…Graft versus host disease was the major complication with grade II-IV acute and chronic incidence to range to about 24% and 13% respectively [186]. Similar results were obtained in other short and long term monitoring studies of HSCT TM patients [7,[182][183][184]187]. Overall, it appears that in general young and non-iron loaded patients with nonunderlying co-morbidities have the highest prospects of OS and TFS from the HSCT TM patients.…”
Section: Endocrine Glandssupporting
confidence: 78%
“…This therapeutic method is subject to suitable donor availability and offers the complete treatment of TM especially for young TM children. The ther-apy has been developed for TM following many years of monitoring and investigations mainly on improving the transplant procedure and also treating the short and long term toxic side effects of transplantation including graft rejection, chimerism, graft versus host disease (GvHD), infections, myeloablative conditioning regimens, the use of matched or mismatched donors and in patients of different ages, iron loading and with different underlying comorbidities [7,8,[182][183][184][185]. In this context, many different factors appear to influence the overall survival (OS) and thalassaemia -free survival (TFS) of HSCT TM patients in different countries and transplantation centers.…”
Section: Endocrine Glandsmentioning
confidence: 99%
“…In the end, 6 studies were included in this review. [9][10][11][14][15][16] The baseline details of the 6 studies are shown in Table 1. One study was from India, whereas all others were from Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Six of them were on adult patients, whereas 2 did not report relevant outcomes and hence were excluded. In the end, 6 studies were included in this review 9–11,14–16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation